Ações e políticas do Estado e da sociedade acerca da geração de renda na Reserva Extrativista Marinha de Soure/Marajó-PA - SANTOS JÚNIOR, Guilherme da Silva (2006)
Income generation is a question that reveals itself plenty of complexities and importance while searching for actions and public policies that permit sustainability in the conservation unit of sustainable use called Extractive Reserve (RESEX). To support this argument, this work makes a connection between the effects of income and the autonomy that rises from it. Besides, it is proposed that, for income to be generated, employment has to be created as well. Various concepts are presented for the historical and theoretical analysis. The link between employment and income is established by means of analysis of the variables collected from field research in Caju-Una, Céu and the Pesqueiro village, the three communities inside the reserve area, the Soure RESEX. Such variables, related to indicators as age, educational level, income and genre, are part of the social-economic profile of the area studied, in wich many social actors coexist. Despite the conflicts caused by the relationship among these actors, it was found an effort to establish points of accordance that facilitate the goal of generating income in the communities, in a way to benefit all actors.